Molecular characterization and multilocus dna barcode-based delimitation of Duranta erecta L. morphotypes from Nigeria (Bangladesh Journal of Plant Taxonomy, 2025)
This study assessed whether the observed morphological variation among eight distinct forms of Duranta erecta in Nigeria reflects true genetic divergence or represents phenotypic plasticity within a single species. The forms are distributed across geo-political zones in Nigeria and were characterized based on leaf coloration, margin types, and branching architecture. These forms exhibit variations in their chemical compositions, suggesting potential differences in their DNA profiles. DNA was extracted from leaf samples of all eight morphological forms, and conventional PCR was employed to amplify three marker regions: ITS, matK, and rbcL. The amplified fragments were visualized on 1% agarose gel electrophoresis, sequenced, and analyzed phylogenetically using MEGA-11. The matK marker exhibited 100% sequence identity, indicating minimal variation among the forms. In contrast, rbcL and ITS displayed 99% sequence identity, with ITS revealing greater polymorphic variation. Phylogenetic tree analysis showed the highest support values for rbcL, followed by ITS and matK. The combined topologies generated from the three markers revealed no significant differences in the evolutionary history of the eight Duranta erecta forms. This result suggests a gene flow among the forms, confirming their classification as a single species.Bangladesh J. Plant Taxon. 32(1): 65-75, 2025 (June)